Return to broiler projects for different size and scale with government incentives - Ismail, Mohd Mansor; Masan, Ilmas Abdurofi; Abdul Wahab, Kamal Hisyam; Gabdo, Bashir Hamman (2015)
The Malaysian Government has been introduced several policies to boost the agricultural performance in the country. The incentive of fiscal policy namely; Pioneer Status (PS), Investment Tax Allowance (ITA), and Accelerated Capital Allowance (ACA) are imposed on various sectors of agricultural venture in order to aid either farming or companies to be profitable. Nevertheless, the lack of effectiveness of the program is still of concern to the agricultural sector in view of the significance of poultry in Malaysia. Therefore, the main objective of the study aims to identify the role of Government incentives in assisting the investment project and analyze the financial feasibility of broiler industry in Peninsular Malaysia from different scales and technological systems. The instruments of financial appraisal are used to calculate the assessment of firm’s financial projection specifically Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period and Profitability Index (PI). The study used questionnaire as a tool of data collection and a face-to-face interview was scheduled for the 309 broiler farmers as respondents. The result reveals that the large farms are more viable with high profitability and rapidly recover its initial investment while the small farms are extremely sensitive to the increase in cost and decrease in revenue. The introduction of Government Incentives positively improves the majority of stockbreeders’ profits. For instance, with a combination between ACA and PS or/and ACA and ITA, the tendency for high financial viability mostly occur in the broiler investment.